Creating and Testing the Reliability of a Family Maltreatment Severity Classification System - Erlanger, Ann C. Eckardt (Journal of interpersonal violence, 2022)
Child maltreatment and intimate partner abuse determinations often include judgments (e.g., severity) that go beyond whether or not the allegations are founded. Severity ratings inform multiple stakeholders (e.g., researchers, policymakers, clinicians, supervisors) and response pathways (e.g., ?differential response? to child maltreatment). However, because severity guidelines typically only provide global direction for raters, these gradations are often of questionable reliability (and thus validity). Extending earlier work developing and implementing reliable and valid family maltreatment substantiation criteria (e.g., Heyman & Slep, 2006, 2009), a classification system for maltreatment severity was created, refined, and field-tested with a sample of clinicians from the largest maltreatment protection agency in the United States The goal was to develop operationalized criteria delineating mild, moderate, and severe maltreatment that could be consistently applied across types of maltreatment, raters, and clinics. To facilitate proper use, a computerized clinical decision support tool for the criteria was created. First, the severity classification system was piloted and refined at four sites throughout the United States. Then, clinicians at these sites (N = 28) and a master reviewer independently rated de-identified cases as part of the clinicians? routine assessments. Agreement between clinicians and the master reviewer was excellent for all types of maltreatment. Implications for practical dissemination are discussed.